GPS-Based Rocket Payload Position Tracking System - Wiharta, Dewa Made; Sastra, Nyoman Putra; Putra, A.A.B. Rama Windhu (JST (Jurnal Sains dan Teknologi), 2023)
The Ministry of Research, Technology and Higher Education Indonesia routinely hosts a competition of payload tracking system placed on a rocket with a Ground Control Station (GCS), a competition known as Kompetisi Muatan Roket dan Roket Indonesia. Fixed GCS antenna causes some problems, including poor communication between payload and GCS, and position detection of the payload. This research was conducted to create a tracking system capable of moving the GCS antenna towards the payload position. In this research, we use two servos to move the antenna. This payload position tracking system works by calculating the azimuth angle of GCS coordinate and of the payload, then converting the azimuth value into the servo angle value. The calculation performs by Arduino Mega 2560 which then commands both the horizontal and vertical  servos to direct the antenna towards the payload position. The experiments are performed with three main tests that are of tracking payload position based on GPS data, of antenna direction movement with servo horizontal motion direction, and of antenna direction movement with servo vertical motion direction. Testing are carried out by laying the payload on a drone and adjust the position and height of the drone manually. Experimental results show that the largest angular difference between the tracking system and the payload is 8 degrees azimuth. The mean angle difference is 4.7 degrees. This angle deviation occurs because the servo angle instruction can only be with an integer value.